Accuracy of Heparin-Binding Protein in Diagnosing Sepsis: A Systematic Review and Meta-Analysis. Issue 1 (January 2021) - Wu, Yi-Luen; Yo, Chia-Hung; Hsu, Wan-Ting; Qian, Frank; Wu, Bo-Sheng; Dou, Qing-Li; Lee, Chien-Chang
Abstract : OBJECTIVES: Existing studies evaluating the accuracy of heparin-binding protein for the diagnosis of sepsis have been inconsistent. We conducted a systematic review and meta-analysis to assess the totality of current evidence regarding the utility of heparin-binding protein to diagnose sepsis in patients with presumed systemic infection. DATA SOURCE: PubMed, Embase, the China National Knowledge infrastructure, and WangFang electronic database were searched from inception to December of 2019. STUDY SELECTION: Two independent reviewers identified eligible studies. Cohort and case-control studies, which measured serum levels of heparin-binding protein among adult patients with suspected sepsis, were eligible for inclusion. DATA EXTRACTION: Two reviewers independently extracted data elements from the selected studies. A bivariate random-effects meta-analysis model was used to synthesize the prognostic accuracy measures. Risk of bias of studies was assessed with Quality Assessment of Diagnostic Accuracy Studies 2 tool. DATA SYNTHESIS: We identified 26 studies with 3, 868 patients in the meta-analysis. Heparin-binding protein had a pooled sensitivity of 0.85 (95% CI, 0.79–0.90) and a pooled specificity of 0.91 (95% CI, 0.82–0.96) for the diagnosis of sepsis. There was low heterogeneity between the studies ( I 2 = 12%), and no evidence of publication bias was detected. Heparin-binding protein had a higher sensitivity and specificity when compared with procalcitonin (0.75 [95% CI, 0.62–0.85] and 0.85 [95% CI, 0.73–0.92]) as well as C-reactive protein (0.75 [95% CI, 0.65–0.84] and 0.71 [95% CI, 0.63–0.77]). Serial measurements of heparin-binding protein also showed that heparin-binding protein levels rose significantly at least 24 hours before a diagnosis of sepsis. CONCLUSIONS: The diagnostic ability of heparin-binding protein is favorable, demonstrating both high sensitivity and specificity in predicting progression to sepsis in critically ill patients. Future studies could assess the incremental value that heparin-binding protein may add to a multimodal sepsis identification and prognostication algorithm for critically ill patients. Abstract : Supplemental Digital Content is available in the text.